(untitled) (Muitas Vozes, 2013)
In an attempt to overcome the structuralist mind set regarding language, a growing body of literature accepts that language does not break down neatly into autonomous, clearly-defined languages. This observation, which is increasingly becoming a mantra of sociolinguistics, is not new at all, despite claims to the contrary. Chomsky (2000) and Davidson (1986) were quite skeptical of the existence of languages. The mythical status of language is concealed by the fact that we have names for languages.